2020
DOI: 10.4103/jdep.jdep_13_19
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis estimating the prevalence, burden, and trend of diabetes mellitus in Saudi Arabia

Abstract: The aim of this study was to determine, using meta-analysis, the prevalence of diabetes mellitus (DM) and to explore the influence of method of diagnosis, DM types, and study year on the prevalence of DM with the view to evaluating the trend and the burden of DM in KSA. Prevalence estimates were derived using a random effect model on carefully selected population-based studies in KSA. The der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…According to estimates from the Ministry of Health, the diagnosed cases of DM surged from around 0.9 million in 1992 to 2.5 million in 2010, indicating an almost threefold increase in incidence within less than two decades [3] . A recent meta-analysis of observational studies conducted in Saudi Arabia revealed point prevalence rates of 20.9% for type 2 DM, 0.9% for type 1 DM, and an overall prevalence of 12.6% [4] .…”
Section: Introductionmentioning
confidence: 99%
“…According to estimates from the Ministry of Health, the diagnosed cases of DM surged from around 0.9 million in 1992 to 2.5 million in 2010, indicating an almost threefold increase in incidence within less than two decades [3] . A recent meta-analysis of observational studies conducted in Saudi Arabia revealed point prevalence rates of 20.9% for type 2 DM, 0.9% for type 1 DM, and an overall prevalence of 12.6% [4] .…”
Section: Introductionmentioning
confidence: 99%
“…The Ministry of Health of Saudi Arabia estimated that the number of people diagnosed with DM rose from approximately 0.9 million people in 1992 to 2.5 million people in 2010, representing an almost 3-fold increase in incidence over less than 2 decades [6]. A recent meta-analysis of observational studies in Saudi Arabia reported type 2 DM, type 1 DM, and overall point prevalence rates of 20.9%, 0.9%, and 12.6%, respectively [7]. DM is associated with morbidity and mortality of public health significance.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The global prevalence of obesity and diabetes has increased in every country and a meta-analysis study reported a 12.6% prevalence of diabetes mellitus in Saudi Arabia. 3 The association between obesity and diabetes is very strong, as it was seen to account for 80% to 85% of Type 2 diabetes mellitus (T2DM). 4 This happens because excess visceral fat accumulation is susceptible to inflammation and cytokine production that lead to dysregulation of adipokines in the body impairing insulin signaling.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 The global prevalence of obesity and diabetes has increased in every country and a meta-analysis study reported a 12.6% prevalence of diabetes mellitus in Saudi Arabia. 3 …”
Section: Introductionmentioning
confidence: 99%